2018
DOI: 10.1002/aocs.12017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Deficit in Bioactive Compounds of Olive Paste and Oil Content

Abstract: The main objective of this study was to evaluate the effect of different deficit irrigation treatments (control, regulated deficit irrigation [RDI]-1, RDI-2, and RDI-3) on the phenolic profile of the olive paste and oil content. Irrigation treatments with more stress water led to a considerable increase in the phenolic compounds of olive paste, especially in oleuropein (60.24%), hydroxytyrosol (82%), tyrosol (195%), and verbascoside (223%) compared to control. A significant increase in the content of total fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…Similar results were found in a recent study performed with “Arbequina” olive oil under water stress during the whole season, where the polyphenol profile and the AA improved with the water deficit (Sena‐Moreno et al, ). In this way, there are previous evidences that tree water status is inversely correlated with polyphenols content in olive oil (Servili et al, ).…”
Section: Resultssupporting
confidence: 89%
“…Similar results were found in a recent study performed with “Arbequina” olive oil under water stress during the whole season, where the polyphenol profile and the AA improved with the water deficit (Sena‐Moreno et al, ). In this way, there are previous evidences that tree water status is inversely correlated with polyphenols content in olive oil (Servili et al, ).…”
Section: Resultssupporting
confidence: 89%
“…A decrease of the concentration was found in P3 for B2. In a previous study performed applying deficit irrigation during all season, polyphenols increased in olive paste as the severity of the applied stress was increased, increasing, for instance, oleuropein, verbascoside, and flavonoids . In our study, the highest changes in the content of polyphenols were found on the iridoid family.…”
Section: Resultssupporting
confidence: 91%
“…25 The lower decrease in some of the antioxidant capacity assays (specially FRAP) compared to TPC loss in both experiments could be explained as a result of the intermediate stage compounds, which were not polyphenols. 26 In this study, a severe irrigation deficit for a short time (A2) and a severe irrigation deficit for a long time and in phase II (pit hardening) (A3) induced a lower content of total phenols; however, other authors 24 found a higher content of total phenols in olive paste with severe water stress. These differences may be mainly due to the genetic component and stage of development of the fruit in which the water deficit is applied.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 60%
See 1 more Smart Citation
“…Several products from olive trees under RDI are being studied as hydroSOStainable ; for instance, “Manzanilla” table olives have been studied [11,12,13]. Arbequina olive oil under water deficit techniques have been previously studied [14,15,16,17,18], but there is not a clear trend on the effect of irrigation on its quality. At this time, there is not a systematic body of knowledge considering agronomic practices, phenological stage during RDI, climatic constraints, etc.…”
Section: Introductionmentioning
confidence: 99%